New record and some morphological data of the Basking Shark, Cetorhinus maximus (Gunnerus, 1765), in the eastern Adriatic - Soldo, Alen (Annales. Series historia naturalis, 1999)
On March 23rd 1999, a Basking Shark, Cetorhinus maximus (Gunnerus, 1765), was caught in gillnet and found by fishermen near Osobljava harbour on the Pelješac peninsula. The paper gives some morphological and meristic data and general information about the species and its occurence in the Adriatic
Keywords: Cetorhinus maximus; morski pes orjak; vzhodni Jadran